2009
DOI: 10.1254/jphs.09018fp
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ranolazine, a Novel Anti-anginal Drug, on Ion Currents and Membrane Potential in Pituitary Tumor GH3 Cells and NG108-15 Neuronal Cells

Abstract: Abstract. Ranolazine, a piperazine derivative, is currently approved for the treatment of chronic angina. However, its ionic mechanisms in other types of cells remain unclear, although it is thought to be a selective blocker of late Na + current. This study was conducted to evaluate the possible effects of ranolazine on Na, and Ca 2+-activated K + current (I K(Ca) ) in pituitary tumor (GH 3 ) cells. Ranolazine depressed the transient and late components of I Na with different potencies. This drug exerted an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 31 publications
3
41
1
Order By: Relevance
“…1. Consistent with our previous observations in GH 3 cells (Liu and Wu 2003;Chen et al 2009;Huang et al 2011), hyperpolarizing voltage pulses induced an instantaneous current followed by a voltageand time-dependent elicitation of a K ? inward current, that is, a deactivating I K(erg) .…”
Section: Effect Of Dehp On I K(erg) In Gh 3 Cellssupporting
confidence: 92%
“…1. Consistent with our previous observations in GH 3 cells (Liu and Wu 2003;Chen et al 2009;Huang et al 2011), hyperpolarizing voltage pulses induced an instantaneous current followed by a voltageand time-dependent elicitation of a K ? inward current, that is, a deactivating I K(erg) .…”
Section: Effect Of Dehp On I K(erg) In Gh 3 Cellssupporting
confidence: 92%
“…6, there was no significant difference in the amplitude of I Na between untreated cells (1.82 ± 0.3 nA, n = 8) and cells treated with SGX (10 μM) (1.81 ± 0.2 nA, n = 8, P  > 0.05). However, in SGX-treated cells, addition of ranolazine (10 μM), a blocker of I Na [27], was capable of suppressing the peak amplitude of I Na significantly from 1.82 ± 0.2 nA to 0.98 ± 0.1 nA (n = 7, P  < 0.05). Therefore, SGX treatment per se did not modify the amplitude of I Na in these cells, while the presence of ranolazine remained effective at suppressing I Na in SGX-treated cells.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…However, in our study, neither tetrodotoxin, ranolazine nor riluzole was demonstrated to have any effects on PALCAR-stimulated I MEP in GH 3 cells. Those compounds are recognized to suppress the amplitude of late Na + currents [32,33]. PALCAR produced a progressive increase of I MEP in GH 3 cells with an EC 50 value of 2.4 µM.…”
Section: Discussionmentioning
confidence: 99%